Detection of Babesia and Theileria parasites in white rhinoceroses (Ceratotherium simum) in the Kruger National Park, and their relation to anaemia - Penzhorn, Barend Louis (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.